Simulation of separating pedestrian flow in T-shaped passage based on guide sign considering unbalanced flow - Li, Yongxing (2021)
This paper analyses the characteristics of separating pedestrian flow in T-shaped passage. Pedestrians would wave and the crowed phenomenon may happen in the connection area of the main passage and branch passage. In order to reduce the pedestrian conflicts, guide sign is set to guide the pedestrians and subconscious strength is introduced to show the effect of guide sign. On this basis, simulation model of separating pedestrian flow in T-shaped passage based on guide sign considering unbalanced flow is established. On the platform of MATLAB software, separating pedestrian flow simulation with the effect of guide sign is realized. Simulations indicate that efficiency of pedestrians passing the passage is improved with the effect of guide sign, suitable position of guide sign is obtained, and compared with the separating pedestrian flow based on guide sign without considering unbalanced flow, the model considering unbalanced flow is better in describing pedestrian distribution.